A Capabilities Approach to the Adjudication of the Right to a Basic Education in South Africa*. Issue 4 (2nd October 2017) - van der Berg, Shanelle
Abstract: This article explores the contours of what a capabilities approach to the adjudication of the right to a basic education in South Africa entails. The right to a basic education fulfils an important role within South Africa's project of transformative constitutionalism, which aims to transform society through processes grounded in law. In turn, transformative constitutionalism's focus on the fundamental constitutional values of freedom, dignity and equality—and its recognition of the relevance of context—resonates with the values underlying the capabilities approach. Certain principles common to transformative constitutionalism and the capabilities approach, namely participation through informational broadening and substantive reasoning through explicitness, should be observed by reviewing courts at all stages of the adjudicative process. Thereafter, the first step of a capabilities approach to adjudication is for courts to interpret the content of the right with reference to the capabilities and functioning outcomes it represents in concrete contexts. Next, a capabilities-based standard of review should be applied to impugned government laws, policy or conduct. Finally, a capabilities approach to remedies should be adopted. This article concludes by evaluating selected education-related judgments by South African courts against the requirements posited by a capabilities approach to adjudication.